Crystal structure of p-xylene@silicalite-1 - In-Chul Hwang (Acta Crystallographica Section E: Crystallographic Communications)
The crystal structure of a highly loaded complex of silicalite-1 (SL-1) with eight molecules of p-xylene per unit cell has been solved by single-crystal X-ray diffraction. In the crystal, four symmetrical Si24O48·2C8H10 subunits per unit cell are observed. The p-xylene molecules sit at two different positions within the SL-1 channels. The first molecule is located at the intersection of the sinusoidal and straight channels, while the second guest molecule is positioned in the center of the double ten-membered ring (10-MR) of the sinusoidal channel.